The effect of Illness representation promoting program on treatment adherence among patients with end stage renal disease receiving hemodialysis - Ali aminuddin Mohd Rasani (Prince of Songkla University., 2016)
Thesis (M.N.S., Nursing Science)--Prince of Songkla University, 2015